Habilidades de pre-cálculo según género en estudiantes de 5 años de una institución educativa inicial del Cercado Callao - Velita Villalba, Pamela (2012)
This research aimed to identify whether there are significant differences in pre calculus skills by gender in children 5 years of an educational institution of Fence-Callao. The comparative descriptive research was conducted with a sample available that consisted of 100 students from five years of an educational institution of Fence- Callao. Test was applied pre calculus Milicic and Schmidt (1995), which assesses math skills through ten dimensions. It was concluded that there are no differences in the abilities of pre calculus students by gender in five years of starting school.